Sur l’impact de l’assurance-chômage dans une économie keynésienne / On the impact of unemployment insurance in a Keynesian economy - Hung, N.; Lefebvre, P. (L'Actualité économique, 1981)
ABSTRACTThis paper deals with involuntary unemployment. We suppose that wages fail to clear markets and undertake a disequilibrium analysis of the effect of unemployment insurance (U.I.) on unemployment and production. The disequilibrium model is so constructed as to take into account the impact of U.I. on all markets. The neo-classical paradigm based on an equilibrium approach is contrasted with the neo-keynesian paradigm which assumes persistent disequilibrium. It is shown in this perspective that U.I. has an impact on unemployment when the latter is keynesian in nature rather than classical. We conclude that in order to evaluate empirically the effect of U.I., the various kinds of unemployment under analysis must be distinguished. We find moreover, that a disequilibrium framework is most appropriate for the study of unemployment.